KEEFEKTIFAN MODEL PEMBELAJARAN PBL BERBANTU MEDIA TEKA- TEKI SILANG TERHADAP HASIL BELAJAR SISWA MATERI IPAS KELAS V SD NEGERI SANGUBANYU 01 BATANG - Lou Warihening Kindra Swastika; Arfilia Wijayanti; Ikha Listyarini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of the Problem-Based Learning (PBL) modelassisted by crossword puzzle media on student learning outcomes in IPAS subjects for fifthgrade students at SD Negeri Sangubanyu 01 Batang. The research method used isquantitative with a pre-experimental design of one group pretest-posttest design. Thepopulation and sample in this study were all 25 students of class V. Data were collectedthrough tests (pretest and posttest), observation, and documentation. The results showedthat there was a significant increase in student learning outcomes after applying the PBLmodel with crossword puzzles as media. The paired sample t-test showed tcount > ttable(7.254 > 2.064) at a significance level of 5%, which means that the treatment given had asignificant effect on learning outcomes. The N-Gain test results showed a value of 0.65which is categorized as moderate. In addition, affective and psychomotor aspects alsoshowed an increase in student activity and learning motivation. Thus, the application of thePBL model assisted by crossword puzzle media is effective in improving student learningoutcomes in IPAS subjects.